Case report: Thoracic schwannoma as a diagnostic pitfall in both 18F-Choline PET/CT and 18F-FDG PET/CT - Amrane, Karim; Le Meur, Coline; Alemany, Pierre; Niel, Clémence; Renault, David; Peillon, Inès; Tissot, Valentin; Abgral, Ronan (Frontiers in Oncology, 2024)
We report increased 18F-FDG uptake in the right posterior mediastinal region in a 70-year-old woman following the discovery of a mass in the aftermath of a bronchitis episode. We also report increased 18F-Choline uptake in the right posterior mediastinal region in a 66-year-old man with newly discovered prostate cancer, which may indicate the presence of mediastinal metastases. Both patients had a thoracic MRI showing an intense gadolinium enhancement in the same region, consistent with thoracic schwannomas, which were subsequently proven histologically. This case highlights that schwannoma is a diagnostic pitfall in both 18F-FDG and 18F-Choline PET/CT.